Mapping forest condition in Europe: Methodological developments in support to forest biodiversity assessments - Marín-Guerrero, Ana Isabel; Abdul Malak, Dania; Bastrup-Birk, Annemarie M.; Chirici, Gherardo; Barbati, Anna; Kleeschulte, Stefan (Elsevier, 2021)
Forest condition, biodiversity, and ecosystem services are strongly interlinked. The biodiversity levels depend to a large extent on the integrity, health, and vitality of forests at the same time as losses of forest biodiversity lead to decreased forest productivity and sustainability. Under this conceptual framework, this study presents a methodology for mapping forest condition at European scale supporting the attainment of the 2020 Aichi Biodiversity Target 5 “the rate of loss of all natural habitats, including forests, is at least halved and where feasible brought close to zero, and degradation and fragmentation is significantly reduced” and the implementation of Sustainable Development Goals (SDG), as well as the EU forest strategy since the sustainable forest management is oriented to support the provision of forest services and to enhance the condition of biodiversity forests’ host. The work presents the developments of an operational indicator at European scale. This spatially explicit information on forest condition can be the baseline map with a 1 km resolution to monitor the state and changes of condition by exposition to pressures and threats. This condition indicator considers structural, functional, and compositional aspects of forest with relevance for health and vitality of species and habitats hosted by forest ecosystems. The methodology implemented used harmonized, published and open datasets. It provided confident results for the assessment of the condition within hemiboreal, temperate and alpine forests, showing the Carpathian, Dinaric Alps and Alps, among others, as hotspots with pre-dominantly good condition. The results were validated with data derived from the reporting for the EU Habitat Directive and explicit dataset on known primary forests in Europe. However, this method underestimated the forest condition in the Mediterranean and Boreal forest types due to data gaps, regional specific characteristics, and design limitations. (...)
Keywords: Biodiversidad forestal; Política ambiental; Forest condition; Forest biodiversity; Mapping; Environmental policy; Europe